Preparation method of controllable and degradable ecological environment-friendly nutrition cup
Through a composite material of starch, polylactic acid and plant fiber, combined with a gradient cross-linking layer and ultraviolet irradiation technology, the durability and degradation rate problems of garden tree seedling pots were solved, and stable support and environmentally friendly degradation of the material during the seedling growth cycle were achieved.
Patent Information
- Application Number
- CN202510952430.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-10-14
AI Technical Summary
Existing garden tree seedling nutrient pots have deficiencies in durability, degradation rate and matching with the seedling growth cycle, making it difficult to meet the needs of large-scale seedling cultivation, and the fiber reinforcement effect is limited during the processing process.
A mixed material of starch, polylactic acid and plant fiber is used, nano-scale inorganic fillers and functional agents are added, and it is formed by a twin-screw extruder and coated with a gradient cross-linking layer to control the degradation rate and mechanical properties. Combined with ultraviolet irradiation, a dense surface layer and a porous inner layer are constructed.
It significantly improves the structural stability and degradation controllability of the nutrient pot, meets the growth needs of seedlings, extends the service life and completely degrades in the natural environment, reducing environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biodegradable materials and garden seedling raising containers, and more specifically, to a method for preparing a controllable and degradable eco-friendly nutrient cup. Background Art
[0002] In the field of garden tree seedling cultivation, biodegradable nutrient pots, as an environmentally friendly alternative to traditional plastic containers, must meet the special requirements of long seedling growth period, strong root expansion, and environmental adaptability after transplanting. Existing nutrient pots based on biodegradable materials still have the following technical limitations when used for large seedling cultivation: First, the durability of the matrix material is difficult to match the growth cycle of seedlings. Since the nursery period of garden seedlings is significantly longer than that of crops, conventional degradable materials are prone to structural relaxation under the dual effects of a continuous hot and humid environment and the pressure of root expansion. Starch-based composite materials have weak interfacial bonding and will produce irreversible deformation under long-term load, causing the container structure to gradually become unstable. Especially in the cultivation of tree seedlings, the attenuation of the material's creep resistance directly affects its ability to restrain the radial expansion of the root system. In addition, the weak bonding interface between plant fibers and the matrix is prone to microscopic damage accumulation under cyclic stress, further accelerating the decline of the material's mechanical properties.
[0003] Secondly, there is insufficient synergy between the degradation behavior and the physiological needs of seedlings. After transplanting, seedlings need to go through multiple growth stages, such as the seedling acclimatization period and the root adaptation period, which requires the nutrient pots to exhibit differentiated degradation characteristics at different times. The existing homogeneous material system is difficult to achieve a functional balance between surface protection and core support: premature degradation of the surface layer will weaken the protection of the new root tips and increase the risk of mechanical damage to the roots; while delayed degradation of the core layer will easily form a physical barrier, interfering with the normal development of lateral roots. The traditional method of adding porogens or adjusting the material ratio often results in a negative correlation between the initial strength of the material and the degradation rate, and cannot take into account both the mechanical support requirements during transplanting and the timely degradation characteristics in the later stage.
[0004] Thirdly, the fiber reinforcement effect is limited by the structural damage during the processing. Garden seedlings' nutrient pots need to have higher longitudinal compressive strength to withstand the static load and dynamic impact brought by multi-layer stacking. In existing processing technologies, plant fibers are prone to breakage and orientation disorder under high-temperature shearing, resulting in a significant reduction in their reinforcement efficiency. Not only are disorderly distributed fibers difficult to effectively transfer stress, but their end interfaces will also become the preferred sites for crack initiation. In addition, the mismatch between the polymer melt flow field and the fiber motion state makes it difficult to maintain the axial arrangement of the fibers during the molding process, which directly affects the anisotropic mechanical properties of the product.
[0005] The technical root causes of these issues can be attributed to the following: at the material system level, the lack of an effective mechanism for synergistic reinforcement at multi-component interfaces leads to premature performance degradation of composite materials under complex service environments; at the molding process level, existing processing methods struggle to achieve a unified approach for maintaining fiber morphology and controlling orientation, restricting the functionality of the reinforcement phase; and at the degradation regulation level, a single material modification approach is unable to establish spatially and temporally differentiated degradation behavior. These technical shortcomings make it difficult for traditional biodegradable nutrient pots to meet the stringent requirements for mechanical durability and degradation chronology required for garden tree cultivation, limiting their practical application in large-scale containerized seedling production. Summary of the Invention
[0006] One purpose of the present invention is to provide a method for preparing a controllable and degradable eco-friendly nutrient cup, which can effectively solve the technical problems of the existing garden seedling nutrient pots such as insufficient long-term support strength, mismatch between degradation rate and seedling growth cycle, etc.
[0007] In order to achieve these objectives and other advantages of the present invention, according to one aspect of the present invention, the present invention provides a method for preparing a controllable and degradable eco-friendly nutrition cup, comprising the following steps: Step 1, starch, polylactic acid and plant fiber are mixed in a mass ratio of (3-5): (4-6): (1-2) to form a biodegradable substrate, wherein the molecular weight of the polylactic acid is 1-2 orders of magnitude higher than that of the starch; 8%-12% of the total mass of a nano-scale inorganic filler, 5%-8% of sodium alginate, 0.5%-2.0% of a sterilizing agent, 0.1%-0.3% of a rooting promoter, and 0.5%-2.0% of potassium humate are added to a biodegradable substrate, and the mixture is stirred and mixed for 30-60 minutes in a temperature range between the starch gelatinization temperature and the polylactic acid glass transition temperature to obtain a mixture having a phase separation structure. Step 2: feeding the mixed material into a twin-screw extruder, where the polylactic acid forms a continuous phase network to wrap the starch particles through the shearing action of the screw, while maintaining the axial orientation of the plant fibers, and injecting the extruded molten material into a mold cavity to form a cylindrical blank; Step 3: dissolving polycaprolactone and polyhydroxyalkanoate in ethyl acetate at a mass ratio of 1:1-3:1 to form a coating liquid, controlling the solid content of the coating liquid to 15%-25%, and forming a coating on the surface of the cylindrical body by an immersion pulling method; adding dicumyl peroxide crosslinking agent accounting for 0.1%-0.5% of the total mass of the polymer to the coating liquid, preheating the impregnated body at 50-70°C and placing it in a UV irradiation box, and irradiating it with UV light with a wavelength of 365 nm and an intensity of 30-50 mW / cm² for 60-180 s to form a cross-linking density gradient structure inside the coating, and finally obtaining a degradable seedling nutrient pot with a controllable degradation layer on the periphery.
[0008] Among them, the starch that can be selected is corn starch or cassava starch, and the gelatinization temperature ranges are 62-72℃ and 58-65℃ respectively. Polylactic acid can be selected with a molecular weight of 1.2×10 5 -1.8×10 5 g / mL 4032D or 2003D. Plant fibers can be bamboo or hemp, with a diameter range of 0.5-1.0 mm. Chitosan quaternary ammonium salt can be used as a sterilant, sodium naphthaleneacetate as a rooting promoter, and potassium humate as a nutrient and rhizosphere improver. A twin-shaft paddle high-speed mixer can be used as the mixing equipment, installed in the constant temperature workstation of the pretreatment workshop. The mixing kettle volume can be adapted for batch production of 200-500 L. A co-rotating parallel twin-screw extruder can be used. The mold can be a cylindrical cavity with axial grooves on the inner wall, with a depth of 0.3-0.6 mm and a width of 0.5-1.0 mm, and 8-12 grooves evenly distributed. A hydraulic drive system can be used for the pressure holding device. The cooling system can be equipped with an annular water cooling jacket, with a water temperature controlled at 10-15°C, installed at the mold outlet. During the process, the mixed material is fed into the extruder via a loss-in-weight feeder, with the screw speed set at 180-220 rpm. As the melt is extruded through the die, the die grooves guide the fibers in axial alignment. The resulting cylindrical body is water-cooled and shaped to a surface roughness Ra ≤ 3.2 μm, with a wall thickness tolerance of ±0.1 mm. Before being transferred to the coating section, the body is blown with compressed air to remove any residual moisture from the surface.
[0009] Preferably, the nanoscale inorganic filler in step 1 is calcium carbonate pretreated with a silane coupling agent, and the pretreatment process comprises mixing calcium carbonate powder with a 2%-3% γ-aminopropyltriethoxysilane ethanol solution in a mass ratio of 1:5-1:8, ultrasonically oscillating at 60-80° C. for 20-30 min, and then drying and crushing to a particle size of 100-200 nm; The stirring and mixing process adopts two-stage temperature control: in the first stage, the temperature is maintained at +5°C to +10°C, the starch gelatinization temperature, for 10-15 minutes to allow the starch granules to fully swell and form a composite gel network with sodium alginate; in the second stage, the temperature is raised to the polylactic acid glass transition temperature range of -20°C to -10°C and stirring is continued for 20-30 minutes to promote the movement of polylactic acid molecular segments and produce mechanical meshing with plant fibers.
[0010] The nano-scale calcium carbonate that can be used is commercially available light calcium carbonate powder produced by precipitation method, with an initial particle size of 50-100nm. For silane coupling agent treatment, γ-aminopropyltriethoxysilane ethanol solution can be used. The ultrasonic treatment equipment can be a constant temperature ultrasonic cleaning tank with a frequency of 40 kHz, installed in the explosion-proof area of the pretreatment workshop, with the treatment temperature set at 70℃±5℃ and the ultrasonic power density at 0.3 W / cm 2, processing time 25±3 min. The drying equipment can be a vacuum drying oven, the temperature is set to 65℃±2℃, and the dried material is processed by a jet mill to a median particle size of 150±30 nm. In the specific implementation, calcium carbonate powder and silane solution are put into a stainless steel reactor, ultrasonic treatment is started and nitrogen protection is continuously introduced. The treated slurry is dehydrated by a plate and frame filter press, and the filter cake is transferred to a vacuum drying oven and dried to a moisture content of ≤0.5%. The crushing process adopts a graded jet mill. The mixing equipment can be a double-layer jacketed stirring kettle, which is assembled in the dust-proof area of the constant temperature workshop. The stirring paddle is a combination of an anchor type and a dispersion disk structure.
[0011] Preferably, the temperature control operation in the first stage of the stirring and mixing process includes: uniformly raising the temperature to the starch gelatinization temperature +5°C to +10°C at a rate of 0.5-1.5°C / min, while continuously introducing carbon dioxide gas into the system to stabilize the pH value at 5.5-6.2, until the storage modulus G' measured by the rheometer reaches 500-800 Pa, thereby determining that a composite gel network is formed; The second stage temperature control operation includes: cooling to the polylactic acid glass transition temperature range of -20°C to -10°C at a rate of 2-3°C / min, adjusting the stirring rate in two stages, maintaining 80-100 rpm for the first 10 minutes to disentangle the polylactic acid molecular chains, then increasing to 120-150 rpm and applying a back pressure of 0.1-0.3 MPa, and stopping stirring when the torque value monitored by the torque rheometer reaches 15-22N·m.
[0012] The carbon dioxide gas inlet system can be connected to the gas distributor at the top of the mixing vessel, with a flow rate controlled at 0.8 L / min ± 0.1 L / min, to maintain a stable pH value between 5.8 and 6.0. A rotational viscometer can be used as the rheometer, mounted on the side of the mixing vessel through an online monitoring port, to monitor the storage modulus in real time. When the G' value reaches 650 ± 50 Pa, gel network formation is determined, triggering an automatic cooling process. Specifically, the premix is placed in a 500 L double-jacketed stirred vessel, and a temperature ramp is initiated while carbon dioxide is introduced. When the temperature reaches 72°C, a sodium alginate solution (3%) is added dropwise at a rate of 5 mL / min using a peristaltic pump. The pH value, as monitored by the online pH meter, stabilizes at 5.9 ± 0.1. Stirring is continued until the rheometer indicates a stable G' value between 620 and 680 Pa. A dual planetary mixer can be used as the mixing equipment. A backpressure control system can be installed at the exhaust port of the mixing vessel. The torque rheometer can be equipped with a digital sensor with a range of 0-30 N·m and an accuracy of ±0.5%. During the cooling phase, low-speed stirring is maintained for the first 10 minutes to disentangle the PLA molecular chains. The speed is then increased and backpressure is applied. Real-time monitoring of the torque curve triggers a shutdown signal when the value reaches 18±1 N·m. The final material temperature at the mixing end is controlled at 43±1°C. Sampling and testing show complete fiber surface coating with no visible agglomerates. Precise temperature control and pH adjustment achieve a starch granule swelling degree of 120%-130%, forming a stable three-dimensional network structure. This two-stage mixing process enhances the mechanical engagement between the PLA molecular chains and the fibers, improving the interfacial bonding strength of the composite material. Torque feedback control ensures mixing uniformity deviation of ≤5%, preventing localized overheating and material degradation.
[0013] Preferably, during the transition period between the first and second stages, polyethylene glycol grafted nano-silica with a particle size of 20-50 nm is added to the mixed system, and the addition amount is 0.5%-1% of the total mass of the mixed system. The cooling rate is controlled to be 2°C / min, so that the nanoparticles are dispersed at the polylactic acid-plant fiber interface. The grafting rate of the polyethylene glycol grafted nano-silica is 15%-25%, and the molecular weight of the polyethylene glycol chain segment is 2000-5000.
[0014] The polyethylene glycol grafted nano-silica that can be used is commercially available surface-modified silica, the grafting rate of which is controlled at 18%-22%, and the molecular weight of the polyethylene glycol chain segment is selected as 3000±500. The adding equipment can be a loss-in-weight micro-feeder, which is installed in the transition conveying pipe between the mixing kettle and the extruder, with a feeding accuracy of ±0.1%. The cooling rate control module can be integrated into the temperature control system, and the cooling slope is set at 2.0℃ / min±0.2℃. The temperature monitoring point is arranged on the outer wall of the pipe through which the material flows. In specific implementation, the feeder is started to add nanoparticles in a pulsed manner, with each feeding interval of 30±5 s. A static mixer and an ultrasonic dispersion probe (frequency 28 kHz, power density 0.5 W / cm 2 ), ensuring uniform dispersion of the nanoparticles. An online particle size analyzer monitors aggregate sizes ≤200 nm, confirming effective particle distribution at the PLA-fiber interface. The amount of nanoparticles added is calculated in real time based on the total material mass, and the control system dynamically adjusts the feed rate based on data from the mixing kettle's weighing sensor. The added nanoparticles form physical entanglements and hydrogen bonds at the interface. The interfacial anchoring effect of the nanoparticles inhibits fiber pullout and enhances the interfacial shear strength between the PLA and fiber.
[0015] Preferably, in step 2, the twin-screw extruder is provided with three temperature gradient zones along the material conveying direction: the temperature of the first zone is 10-20°C above the starch gelatinization temperature, the temperature of the second zone is 30-50°C above the glass transition temperature of polylactic acid, and the temperature of the third zone is 5-10°C below the melting temperature of polylactic acid.
[0016] Preferably, the inner surface of the mold in step 2 is provided with an array of grooves parallel to the axial direction, the groove depth is 0.5-1 times the diameter of the plant fiber, and the molding is performed under a pressure of 0.5-1.5 MPa to allow the plant fibers to be arranged in a direction along the grooves.
[0017] The inner surface of the mold can be machined with 8-12 parallel axial grooves. The groove depth is set to 0.8 times the plant fiber diameter ± 0.1 (for example, a bamboo fiber diameter of 0.5 mm corresponds to a depth of 0.4 mm), with a width of 0.6 mm ± 0.1 and a spacing of 1.2 mm ± 0.2. The mold material can be H13 mold steel with a hard chrome plated surface (thickness 0.02-0.03 mm), and assembled to the outlet flange of the twin-screw extruder. The pressure holding system can use a hydraulic drive device with a pressure setting of 1.0 MPa ± 0.1, equipped with a digital pressure sensor (range 0-5 MPa, accuracy ± 0.5%). The hydraulic cylinder can be installed above the mold at the ejection mechanism.
[0018] Preferably, in step three, the degradation rate is controlled by adjusting the mass ratio of polycaprolactone to polyhydroxyalkanoate, the ultraviolet irradiation time and the coating thickness, wherein each increase of 1 unit in the mass ratio corresponds to an extension of the degradation time by 200-300 days, and each increase of 60s in the ultraviolet irradiation time corresponds to a shortening of the degradation time by 100-150 days; each increase of 50 μm in the coating thickness extends the degradation time by 180-220 days.
[0019] Polycaprolactone can be a linear polymer with a number average molecular weight (Mn) of 80,000-100,000, and polyhydroxyalkanoates can be a PHBHHx copolymer with an Mn of 40,000-50,000. The coating liquid preparation equipment can be a magnetic stirring kettle installed in the constant temperature compartment of the coating section, with the stirring rate set to 300±50 rpm. The UV irradiation equipment can be a crawler-type curing machine with light intensity partitioning, with the front section light intensity set to 55±5 mW / cm 2 , posterior segment 25±3 mW / cm 2 The irradiation box length is suitable for a 10-15 second dwell time. The dipping tank can be equipped with a lifting mechanism and assembled at the starting end of the coating line.
[0020] Preferably, the specific operation of controlling the degradation rate in step 3 satisfies the following relationship: Degradation days D = 300 × (PCL / PHA) + 4H - 1.5T + 200 ± 60; PCL / PHA is the mass ratio of polycaprolactone to polyhydroxyalkanoate, ranging from 1 to 3; H is the coating thickness, ranging from 60 to 300 μm; and T is the UV irradiation time, ranging from 60 to 180 s.
[0021] The degradation period formula D = 300 × (PCL / PHA) + 4H - 1.5T + 200 ± 60 in this technical solution is a mathematical model established through regression analysis of experimental data to predict the degradation period of biodegradable seedling pots. In the formula, the weights of each parameter and their mechanism of action are as follows: 1. Parameter weights and action mechanisms PCL / PHA mass ratio (weight +300): Polycaprolactone (PCL) degrades slowly due to its high crystallinity, while polyhydroxyalkanoates (PHA) are susceptible to microbial degradation due to their amorphous structure. For every 1 unit increase in the mass ratio (e.g., from 1:1 to 2:1), the degradation cycle is extended by approximately 300 days. For example, at a PCL / PHA ratio of 3, PCL forms a continuous phase, significantly slowing degradation. At a PCL / PHA ratio of 1, PHA dominates the degradation cycle, shortening it to approximately one year.
[0022] Coating thickness (weight + 4 / μm): Coating thickness affects degradation by physically blocking moisture and microbial penetration. Every 50 μm increase in thickness increases the moisture diffusion path and delays degradation by approximately 200 days. For example, a 200 μm coating will degrade 560 days longer than a 60 μm coating.
[0023] UV irradiation time (weight -1.5 / second): Extended UV irradiation time has a dual effect: on the one hand, it increases the crosslink density gradient within the coating, promoting later disintegration; on the other hand, excessive irradiation can deplete the crosslinker and induce photodegradation. For example, increasing the irradiation time from 60 seconds to 180 seconds shortens the degradation period by 180 days.
[0024] The constant term (200 ± 60 days) represents the natural degradation period of the uncoated substrate (pure PLA / starch composite) under standard soil conditions. The ±60-day error range accounts for environmental fluctuations (e.g., temperature ±3°C, humidity ±10%) and differences in microbial activity.
[0025] This formula, developed through zoned UV irradiation to create a "dense surface layer-porous inner layer" structure, balances initial protection with later degradation. By incorporating material ratios, coating thickness, and irradiation processes into a unified mathematical model, the resulting predictions are highly accurate, providing a scientific basis for the customized production of biodegradable seedling containers and significantly improving the product's compatibility with environmental requirements.
[0026] Preferably, the ultraviolet irradiation process in step 3 comprises: In the first stage, the irradiation intensity is 50-60mW / cm² for the first 1 / 3 of the total treatment time, so that the surface temperature of the coating reaches 40℃-50℃, forming a dense surface layer; The second stage is 20-30mW / cm 2 The irradiation intensity is completed for the remaining time, and the internal temperature of the coating is controlled at 30℃-40℃ to form a porous inner layer.
[0027] The present invention has at least the following beneficial effects: First, the preparation method of the present invention significantly improves the comprehensive performance of garden seedling pots through the synergistic effect of multiphase composite and gradient regulation. The formation of a continuous phase network of polylactic acid in the matrix material effectively enhances structural stability. Combined with the fiber axial orientation design, the longitudinal compressive strength is significantly better than that of traditional products, meeting the requirements of multi-layer stacking and transportation. The combination of two-stage temperature control and interface modification technology improves component compatibility and inhibits mechanical degradation in hot and humid environments, ensuring structural integrity during the seedling cultivation cycle. The construction of a gradient cross-linked coating enables precise temporal and spatial control of degradation behavior. The dense surface structure provides protection during the initial transplanting period, while the internal porous structure promotes synergistic degradation in the later stage, effectively matching the rhythm of seedling root expansion. The establishment of a quantitative model of process parameters significantly improves the efficiency of degradation cycle design. By dynamically controlling the coating composition, thickness, and irradiation conditions, the degradation behavior is well adapted to the soil environment. The combination of mold flow optimization and melt phase control reduces fiber processing damage while improving the orientation ratio and enhancing the anisotropic mechanical properties of the composite material. The introduction of an interface compatibilizer alleviates thermal stress concentration and extends the service life of the product under cyclic loading. The overall solution achieves synergistic optimization in terms of material durability, degradation controllability and processing stability, providing reliable technical support for containerized cultivation of large seedlings.
[0028] Second, by adding three functional components, chitosan quaternary ammonium salt, sodium naphthaleneacetate, and potassium humate, to the base material, the nutrient pots are further endowed with auxiliary beneficial effects of inhibiting seedling diseases, promoting root development, and improving the rhizosphere microenvironment, which helps to improve the health of seedlings and the survival rate of transplantation.
[0029] Third, the biodegradable, eco-friendly nutrient cups produced by this invention utilize biodegradable components for both their base material (starch / PLA / plant fiber) and functional coating. At the end of their useful life, they are decomposed by microorganisms in the natural environment, ultimately converting into carbon dioxide, water, and biomass, without causing persistent environmental pollution. This fundamentally addresses the serious environmental problem of traditional petroleum-based plastic nutrient pots, which, due to their inability to degrade, leave long-term soil residues, disrupt ecological balance, and contribute to microplastic pollution chains. This provides environmentally friendly technical support for the sustainable development of the landscaping industry.
[0030] Fourth, unlike the uncontrollable degradation behavior of traditional homogeneous biodegradable materials, this invention achieves precise design of the degradation cycle by precisely controlling the coating component ratio (polycaprolactone / polyhydroxyalkanoate mass ratio), coating thickness, and UV irradiation conditions. This ensures that the degradation rate closely matches the root growth cycle (seedling acclimatization, adaptation, and rapid growth) of different tree species. This "on-demand degradation" property not only provides stable support during the initial seedling raising and transplanting phases, but also disintegrates in a timely manner later to avoid hindering root expansion. Crucially, this feature offers unique value for afforestation in specialized environments, such as high-altitude cold regions and ecologically sensitive areas like Tibet. Parameter control ensures structural stability during the seedling raising phase (e.g., up to two years). Once the seedlings are transplanted to the afforestation site, the pre-set degradation process begins upon contact with the soil. Simultaneously, nutrients such as potassium humate loaded in the substrate are gradually released as they degrade, creating a "nutrient relay" effect, helping the seedlings establish and survive in the cold and barren conditions of the site. Ultimately, this achieves "zero-burden" afforestation—fully integrated into the natural cycle and avoiding any residual pollution to the fragile native environment of Tibet. This significantly improves the ecological adaptability, resource utilization efficiency and applicability of container seedling cultivation in environmentally sensitive areas. Other advantages, objectives and features of the present invention will be reflected in part by the following description and will also be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0031] The present invention will be further described in detail below in conjunction with specific embodiments so that those skilled in the art can implement the invention with reference to the description.
[0032] It should be understood that terms such as “having”, “including” and “comprising” used herein do not preclude the existence or addition of one or more other elements or combinations thereof.
[0033] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0034] Example 1 A method for preparing a controllable and degradable eco-friendly nutrition cup, the specific steps are as follows: Step 1: Corn starch (gelatinization temperature 68 ° C), polylactic acid 4032D (molecular weight 1.5 × 10 5g / mol, glass transition temperature 58°C, melting temperature 172°C) and plant fibers were mixed in a mass ratio of 4:5:1.5 to form a biodegradable matrix. To this matrix was added 10% by weight of nano-calcium carbonate (pretreated with γ-aminopropyltriethoxysilane), 6.5% sodium alginate, 1.2% chitosan quaternary ammonium salt, 0.2% sodium naphthalene acetate, and 1.0% potassium humate. The mixture was stirred in two stages between 70°C (starch gelatinization temperature + 8°C) and 58°C (polylactic acid glass transition temperature). The first stage was maintained at 75°C for 12 minutes to allow the starch to fully swell and form a composite gel network. The second stage was cooled to 48°C (polylactic acid Tg - 10°C) and stirred for 25 minutes, resulting in a mixture with a continuous phase separation structure.
[0035] Step 2: The mixture is fed into a twin-screw extruder, with the three temperature sections set at 83°C (starch gelatinization temperature + 15°C), 98°C (40°C above the PLA Tg), and 165°C (7°C below the PLA melting temperature). The screw shears the PLA into a continuous phase that encapsulates the starch granules. The molten material is then injected into a mold with axial grooves on the inner wall (depth 0.8 times the fiber diameter). The extruder is then formed into a cylindrical body under a holding pressure of 1.0 MPa, achieving an axial fiber orientation of 85%.
[0036] Step 3: Dissolve polycaprolactone and polyhydroxyalkanoate in ethyl acetate at a 1:1 mass ratio to create a coating solution with a 20% solids content. Add 0.3% dicumyl peroxide. The green body is dipped and pulled to form a 60μm coating. After preheating to 60°C, the green body is placed in a UV irradiation chamber and irradiated at 55mW / cm² for 60 seconds to form a dense surface layer. Then, irradiated at 25mW / cm² for 120 seconds to create a porous inner layer, ultimately producing a nutrient pot with a gradient cross-linked structure on the periphery.
[0037] Example 2 A method for preparing a controllable and degradable eco-friendly nutrition cup, the specific steps are as follows: Step 1: Combine cassava starch (gelatinization temperature 63°C), polylactic acid 2003D (molecular weight 1.8×10 5 g / mol, glass transition temperature 55℃, melting temperature 170℃) and bamboo fiber (diameter 0.6 mm) were mixed in a mass ratio of 4:5:1.5 to form a biodegradable substrate.
[0038] 9% of the total mass of nano-scale calcium carbonate (pretreated with γ-aminopropyltriethoxysilane), 7% of sodium alginate, 0.8% of chitosan quaternary ammonium salt, 0.16% of sodium naphthaleneacetate, and 1.5% of potassium humate were added to the substrate.
[0039] The first stage of temperature control operation: The temperature was uniformly raised to 68°C (starch gelatinization temperature + 5°C) at a rate of 1.0°C / min, and carbon dioxide gas was introduced at a flow rate of 0.8 L / min to stabilize the pH of the system at 5.8-6.0.
[0040] Continue stirring until the storage modulus G' detected by the rheometer reaches 700±50 Pa (composite gel network is formed).
[0041] Second stage temperature control operation: The temperature was lowered to 45°C (PLA Tg - 10°C) at a rate of 2.5°C / min. The stirring rate was maintained at 90 rpm for the first 10 minutes to disentangle the PLA molecular chains, and then increased to 130 rpm and a back pressure of 0.2 MPa was applied.
[0042] Stop stirring when the torque value monitored by the torque rheometer reaches 18±1 N·m.
[0043] Transitional modification: At the beginning of the cooling stage, 0.8% polyethylene glycol-grafted nanosilica (particle size 30 ± 10 nm, grafting rate 20%, PEG molecular weight 3000) was added to the mixed system.
[0044] The cooling rate was controlled at 2°C / min, and an ultrasonic dispersion probe (frequency 28 kHz) was used to assist the uniform dispersion of nanoparticles at the polylactic acid-bamboo fiber interface.
[0045] Step 2: Feed the mixed material into the co-rotating parallel twin-screw extruder and set three temperature gradients: The first zone is 73°C (starch gelatinization temperature + 10°C), the second zone is 95°C (40°C above the Tg of polylactic acid), and the third zone is 165°C (5°C below the melting temperature of polylactic acid).
[0046] The molten material was injected into a mold with 12 axial grooves (depth 0.5 mm, width 0.8 mm) on the inner wall, and a cylindrical blank was formed under a holding pressure of 1.2 MPa. The fiber axial orientation degree reached 88%.
[0047] Step 3: Dissolve polycaprolactone (PCL, Mn=90,000) and polyhydroxyalkanoate (PHA, PHBHHx type, Mn=45,000) in ethyl acetate at a mass ratio of 2:1 to prepare a coating solution with a solid content of 22%, and add 0.4% diisopropylbenzene peroxide as a crosslinker.
[0048] The green body is dipped and pulled to form a 150 μm uniform coating, which is then preheated to 65°C and placed in a UV irradiation box: Phase 1: 55 mW / cm 2Intensive irradiation for 50 seconds (the first 1 / 3 of the total time) to form a dense surface layer (temperature reaches 45°C); Second stage: 25 mW / cm 2 The film was irradiated at high intensity for 100 seconds and the internal temperature was controlled at 35°C to form a porous inner layer.
[0049] Example 3 The difference from Example 1 is that in step 3, polycaprolactone (PCL) and polyhydroxyalkanoate (PHA) are mixed at a mass ratio of 1.2:1, the coating thickness is set to 120 μm, and the UV irradiation time is controlled to 150 seconds. The specific operation is as follows: PCL and PHA are dissolved in ethyl acetate at a mass ratio of 1.2:1 to prepare a coating solution with a solid content of 18%, and the viscosity is adjusted to 420 mPa·s. The green body is dipped and pulled at a speed of 12 cm / min to form a uniform coating with a thickness of 120 μm, and then the coating is heated at 55 mW / cm 2 Irradiate for 50 seconds, then irradiate for 100 seconds at 25 mW / cm². Finally, a nutrient pot with a gradient cross-linked structure on the periphery was produced.
[0050] Example 4 The difference from Example 1 is that a PCL / PHA mass ratio of 2.0:1 is used, the coating thickness is increased to 200 μm, and the UV irradiation time is shortened to 100 seconds. The solid content of the coating solution is increased to 22% during preparation, and the viscosity is controlled to 480 mPa·s. The dipping and pulling speed is reduced to 8 cm / min to ensure that the coating thickness uniformity deviation is less than 5%. The UV irradiation is carried out at 58 mW / cm 2 Treatment for 33 seconds, the latter part at 28 mW / cm 2 Processing 67 seconds.
[0051] Example 5 The difference from Example 1 is that the PCL / PHA mass ratio is increased to 2.8:1, the coating thickness is set to 280 μm, and the UV irradiation time is reduced to 60 seconds. The solid content of the coating liquid is 25%, and the viscosity is increased to 550 mPa·s. The dipping and pulling speed is further reduced to 5 cm / min, and the mold is preheated to 65°C to reduce sagging. The UV irradiation is carried out at 60 mW / cm 2 The treatment lasts for 20 seconds to form a dense surface layer, followed by a treatment at 20 mW / cm² for 40 seconds.
[0052] Comparative Example 1 A method for preparing a degradable nutrient pot, the specific steps are as follows: Step 1: Corn starch (same as in Example 1, gelatinization temperature 68°C), polylactic acid 4032D (same as in Example 1, molecular weight 1.5×10 5g / mol) and plant fibers were mixed in a mass ratio of 3:6:1. Untreated calcium carbonate powder (particle size 1-5 μm) and 5% sodium alginate were added to the substrate at 10% of the total mass. The mixture was stirred at 75°C for 40 minutes under single-stage temperature control. pH control and rheological monitoring were not performed.
[0053] Step 2: Feed the mixed material into a single-screw extruder and set the homogenization temperature to 145°C. The molten material is injected into a smooth mold without grooves and formed into a cylindrical body under a pressure of 0.8 MPa.
[0054] Step 3: Use the same polycaprolactone / polyhydroxyalkanoate (2:1) coating solution as in Example 1, but omit the UV irradiation gradient control and directly apply 30mW / cm 2 Irradiate with uniform intensity for 120 seconds.
[0055] The nutrient pots of the same specifications prepared in Examples 1-5 and Comparative Example 1 were taken as samples and the following tests were performed respectively: Longitudinal compressive strength: universal testing machine (GB / T 1041-2018), loading rate 5 mm / min.
[0056] Degradation performance: Soil burial test (ASTM D5988-18), temperature 25±2℃, humidity 60%±5%, regular sampling to detect mass loss rate and compressive strength retention rate.
[0057] Mass loss rate: Mass loss rate = (W0-W t ) / W0×100%; Compressive strength retention rate: Retention rate = F t / F0×100%.
[0058] Cross-linking density gradient of coating: swelling test (immersion in toluene for 24 h), and cross-linking degree was determined by stratification (surface layer / inner layer).
[0059] Degradation days: The end point of complete degradation is when the mass loss rate is ≥80% and the compressive strength retention rate is ≤20%.
[0060] The initial performance test results of the samples are shown in Table 1: Table 1. Comparison of initial performance test results *Note: Cross-linking gradient difference = surface cross-linking degree - inner cross-linking degree.
[0061] The degradation performance comparison results are shown in Table 2: Table 2. Comparison of degradation performance test results Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Quality loss rate (%) (24 months) 98 43 71 55 38 98 Compressive strength retention rate (%) (24 months) 6 41 22 49 73 5 Theoretical degradation time 470±60 days 1175±60 days 815±60 days 1450±60 days 2070±60 days - Measured degradation time 16 months 40 months 27 months 48 months 69 months 12 months From the results in Table 1 and Table 2, it can be seen that the longitudinal compressive strength of Examples 1-5 is significantly higher than that of Comparative Example 1. The main reasons include: Fiber directional reinforcement: The groove mold in the embodiment induces the fiber to axially orientate to form a reinforcement skeleton, while the fibers in comparative example 1 are disorderly distributed and the stress transfer efficiency is low.
[0062] Filler modification effect: The example uses silane-treated nano-calcium carbonate to inhibit agglomeration and improve the matrix-filler interface bonding.
[0063] Coating synergy: The gradient cross-linked coating in Example 1 delayed the initial mechanical degradation through the dense surface structure, while the compressive resistance retention rate of the uniform coating in Comparative Example 1 was only 5% after 24 months.
[0064] The results of degradation days proved that the regulation law was consistent with the formula prediction.
[0065] In Comparative Example 1, the degradation time cannot be controlled due to the lack of gradient structure design, unoptimized interface bonding, and the nonlinear relationship between process parameters and degradation behavior.
[0066] Examples 1-5, through gradient cross-linking coating design, fiber axial orientation, and interface modification, achieve precise control of degradation cycles and mechanical properties, meeting the diverse needs of garden seedlings. Process deficiencies in Comparative Example 1 (homogeneous structure, disordered fibers, and unmodified filler) demonstrate the necessity of the core technologies (gradient irradiation, oriented molding, and filler treatment). This technical solution provides reliable theoretical support and a process paradigm for the engineering application of degradable seedling containers.
[0067] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and examples shown and described herein.
Claims
1. A method for preparing a controllable and degradable eco-friendly nutritional cup, characterized in that: The following steps are involved: Step 1, starch, polylactic acid and plant fiber are mixed in a mass ratio of (3-5): (4-6): (1-2) to form a biodegradable substrate, wherein the molecular weight of the polylactic acid is 1-2 orders of magnitude higher than that of the starch; 8%-12% of the total mass of a nano-scale inorganic filler, 5%-8% of sodium alginate, 0.5%-2.0% of a sterilizing agent, 0.1%-0.3% of a rooting promoter, and 0.5%-2.0% of potassium humate are added to a biodegradable substrate, and the mixture is stirred and mixed for 30-60 minutes in a temperature range between the starch gelatinization temperature and the polylactic acid glass transition temperature to obtain a mixture having a phase separation structure. Step 2: feeding the mixed material into a twin-screw extruder, where the polylactic acid forms a continuous phase network to wrap the starch particles through the shearing action of the screw, while maintaining the axial orientation of the plant fibers, and injecting the extruded molten material into a mold cavity to form a cylindrical blank; Step 3: dissolving polycaprolactone and polyhydroxyalkanoate in ethyl acetate at a mass ratio of 1:1-3:1 to form a coating liquid, controlling the solid content of the coating liquid to be 15%-25%, and forming a coating on the surface of the cylindrical body by an immersion pulling method; adding dicumyl peroxide crosslinking agent accounting for 0.1%-0.5% of the total mass of the polymer to the coating liquid, preheating the impregnated body at 50-70°C and placing it in a UV irradiation box, using a wavelength of 365 nm and an intensity of 30-50 mW / cm 2 The coating was irradiated with ultraviolet light for 60-180 s to form a cross-linked density gradient structure inside the coating, and finally a degradable seedling pot with a controllable degradation layer on the periphery was obtained.
2. The method for preparing the controllable and degradable eco-friendly nutritional cup according to claim 1, wherein: In step 1, the nanoscale inorganic filler is calcium carbonate pretreated with a silane coupling agent. The pretreatment process includes mixing calcium carbonate powder with a 2%-3% γ-aminopropyltriethoxysilane ethanol solution in a mass ratio of 1:5-1:8, ultrasonically oscillating at 60-80°C for 20-30 minutes, and then drying and crushing to a particle size of 100-200 nm. The stirring and mixing process adopts two-stage temperature control: in the first stage, the temperature is maintained at +5°C to +10°C, the starch gelatinization temperature, for 10-15 minutes to allow the starch granules to fully swell and form a composite gel network with sodium alginate; in the second stage, the temperature is raised to the polylactic acid glass transition temperature range of -20°C to -10°C and stirring is continued for 20-30 minutes to promote the movement of polylactic acid molecular segments and produce mechanical meshing with plant fibers.
3. The method for preparing the controllable and degradable eco-friendly nutrition cup according to claim 2, characterized in that: The first stage temperature control operation of the stirring and mixing process includes: uniformly raising the temperature to the starch gelatinization temperature +5°C to +10°C at a rate of 0.5-1.5°C / min, while continuously introducing carbon dioxide gas into the system to stabilize the pH value at 5.5-6.2, until the storage modulus G' measured by the rheometer reaches 500-800 Pa, thereby determining that a composite gel network is formed; The second stage temperature control operation includes: cooling to the polylactic acid glass transition temperature range of -20°C to -10°C at a rate of 2-3°C / min, adjusting the stirring rate in two stages, maintaining 80-100 rpm for the first 10 minutes to disentangle the polylactic acid molecular chains, then increasing to 120-150 rpm and applying a back pressure of 0.1-0.3 MPa. Stirring is stopped when the torque value monitored by the torque rheometer reaches 15-22 N·m.
4. The method for preparing the controllable and degradable eco-friendly nutritional cup according to claim 3, characterized in that: During the transition period between the first and second stages, polyethylene glycol-grafted nano-silica with a particle size of 20-50 nm is added to the mixed system in an amount of 0.5%-1% of the total mass of the mixed system. The cooling rate is controlled at 2°C / min to disperse the nanoparticles at the polylactic acid-plant fiber interface. The grafting rate of the polyethylene glycol-grafted nano-silica is 15%-25%, and the molecular weight of the polyethylene glycol chain segment is 2000-5000.
5. The method for preparing the controllable and degradable eco-friendly nutritional cup according to claim 1, wherein: In step 2, the twin-screw extruder is set with three temperature gradient zones along the material conveying direction: the temperature of the first zone is 10-20°C above the starch gelatinization temperature, the temperature of the second zone is 30-50°C above the glass transition temperature of polylactic acid, and the temperature of the third zone is 5-10°C below the melting temperature of polylactic acid.
6. The method for preparing the controllable and degradable eco-friendly nutrition cup according to claim 1, characterized in that: In step 2, the inner surface of the mold is provided with a groove array parallel to the axial direction, the groove depth is 0.5-1 times the diameter of the plant fiber, and the mold is pressed under a pressure of 0.5-1.5 MPa to make the plant fibers arranged in a direction along the groove.
7. The method for preparing the controllable and degradable eco-friendly nutritional cup according to claim 1, wherein: In step three, the degradation rate is controlled by adjusting the mass ratio of polycaprolactone to polyhydroxyalkanoate, ultraviolet irradiation time and coating thickness. For every 1 unit increase in the mass ratio, the degradation time is extended by 200-300 days, and for every 60 s increase in ultraviolet irradiation time, the degradation time is shortened by 100-150 days. For every 50 μm increase in coating thickness, the degradation time is extended by 180-220 days.
8. The method for preparing the controllable and degradable eco-friendly nutritional cup according to claim 7, characterized in that: The specific operation of controlling the degradation rate in step 3 satisfies the following relationship: Degradation days D = 300 × (PCL / PHA) + 4H - 1.5T + 200 ± 60; Where PCL / PHA is the mass ratio of polycaprolactone to polyhydroxyalkanoate, ranging from 1 to 3; H is the coating thickness, ranging from 60 to 300 μm; T is the UV irradiation time, ranging from 60 to 180 s.
9. The method for preparing the controllable and degradable eco-friendly nutritional cup according to claim 8, characterized in that: The UV irradiation process in step 3 includes: In the first stage, the irradiation intensity is 50-60 mW / cm² for the first 1 / 3 of the total treatment time, so that the surface temperature of the coating reaches 40℃-50℃, forming a dense surface layer; The second stage is 20-30 mW / cm 2 The irradiation intensity is completed for the remaining time, and the internal temperature of the coating is controlled at 30℃-40℃ to form a porous inner layer.
Citation Information
Cited By
Polyhydroxyalkanoate (PHA) water-based water-blocking coating molded pulp seedling pot containing inorganic filler and polymer blend and preparation method thereof
CN121730120A